Origin, evolution, and distribution of the molecular machinery for biosynthesis of sialylated lipooligosaccharide structures in Campylobacter coli - Alejandra Culebro (Nature Portfolio, 2018)
Abstract Campylobacter jejuni and Campylobacter coli are the most common cause of bacterial gastroenteritis worldwide. Additionally, C. jejuni is the most common bacterial etiological agent in the autoimmune Guillain-Barré syndrome (GBS). Ganglioside mimicry by C. jejuni lipooligosaccharide (LOS) is the triggering factor of the disease. LOS-associated genes involved in the synthesis and transfer of sialic acid (glycosyltranferases belonging to family GT-42) are essential in C. jejuni to synthesize ganglioside-like LOS. Despite being isolated from GBS patients, scarce genetic evidence supports C. coli role in the disease. In this study, through data mining and bioinformatics analysis, C. coli is shown to possess a larger GT-42 glycosyltransferase repertoire than C. jejuni. Although GT-42 glycosyltransferases are widely distributed in C. coli population, only a fraction of C. coli strains (1%) are very likely able to express ganglioside mimics. Even though the activity of C. coli specific GT-42 enzymes and their role in shaping the bacterial population are yet to be explored, evidence presented herein suggest that loss of function of some LOS-associated genes occurred during agriculture niche adaptation.